Исследования на новом участке херсонесского некрополя в 2008 г. - Туровский, Е.Я.; Филиппенко, А.А. (Археологічні дослідження в Україні, 2010)
The paper concerns excavations of a new section of necropolis in Tauric Chersonesos. Five Hellenistic period ground graves and three Roman period crypts were studied. One crypt contained no inventory; while the other two included materials from the 1st c. to the 10th c. Walls of one of the crypts were painted with the depictions of wild animals hunting from horseback.